Geological controls on bedrock topography and ice sheet dynamics in the Wilkes Subglacial Basin sector of East Antarctica - Fausto Ferraccioli; Egidio Armadillo; Duncan Young; Donald Blankenship; Tom Jordan; Martin Siegert (European Geophysical Society, 2017)
The Wilkes Subglacial Basin extends for 1,400 km into the interior of East Antarctica and hosts several major glaciers that drain a large sector of the East Antarctic Ice Sheet. The deep northern Wilkes Subglacial Basin underlies the catchments of the Matusevich, Cook, Ninnis and Mertz Glaciers, which are largely marine-based and hence potentially particularly sensitive to past and also predicted future ocean and climate warming. Sediment provenance studies suggest that the glaciers flowing in this region may have retreated significantly compared to their modern configuration, as recently as the warm mid-Pliocene interval, potentially contributing several m to global sea level rise (Cook et al.,Nature Geosci., 2013). Here we combine airborne radar, aeromagnetic and airborne gravity observations collected during the inter- national WISE-ISODYN and ICECAP aerogeophysical campaigns with vintage datasets to help unveil subglacial geology and deeper crustal architecture and to assess its influence on bedrock topography and ice sheet dynamics in the northern Wilkes Subglacial Basin. Aeromagnetic images reveal that the Matusevich Glacier is underlain by a ca 480 Ma thrust fault system (the Exiles Thrust), which has also been inferred to have been reactivated in response to intraplate Cenozoic strike-slip faulting. Further to the west, the linear Eastern Basins are controlled by the Prince Albert Fault System. The fault system continues to the south, where it provides structural controls for both the Priestley and Reeves Glaciers. The inland Central Basins continue in the coastal area underlying the fast flowing Cook ice streams, im- plying that potential ocean-induced changes could propagate further into the interior of the ice sheet. We propose based on an analogy with the Rennick Graben that these deep subglacial basins are controlled by the underlying horst and graben crustal architecture. Given the interpreted subglacial distribution of Beacon sediments and Ferrar tholeiites and uplifted Ross-age basement blocks, ...